Peran Bahasa Dalam Pembentukan Identitas Budaya Di Indonesia - Kevin Rewardi Harefa; Kristian Harapan Harefa (CV. SINAR HOWUHOWU, 2024)
As a medium of expression and communication that captures the rich history and culture of the country, language plays a crucial part in the development of Indonesian cultural identity. In this regard, the article